Determinan Makro Ekonomi Yang Mempengaruhi Nilai Aktiva Bersih Reksadana Syariah - Azzahra, Khoirunnisa; Arianti, Baiq Fitri (Universitas Gorontalo, 2021)
The purpose of this study was to determine and analyze macroeconomic factors such as inflation, exchange rates and Indonesian Sharia bank certificates on Net Asset Value. Sources of data obtained from OJK and BI with 5 years of observation, The sampling technique used in this study is non-probability sampling, that is by using saturated sampling with a total sample of 60 data. The method used in this research is descriptive statistical analysis, classical assumption test, multiple linear regression analysis and hypothesis testing. By using the Statistical Package for the Social Science (SPSS) version 22.0 For Windows. The results of this study indicate that inflation has no effect on the value of net assets, while the exchange rate and SBIS partially affect the value of net assets. Simultaneously inflation, exchange rate and SBIS affect the net asset value. Net asset value (NAV) is important in mutual funds, because net asset value is one of the benchmarks in unifying mutual fund performance, the net asset value of equity/unit development mutual funds has increased, and vice versa decreased the value of initial mutual fund net assets/unit participation has decreased.